Nutritive Value Improvement and Utilization of Rice Straw in a Total Mixed Ration for Lambs - Hasan, Md. Mainul (2006)
In the nutritional assessment study - two popular rice varieties in Malaysia namely, MR 185 and MR 219 were examined. Significant variations in straw nutritional composition were observed between plant fractions of rice varieties. Variations were also observed between the cut and stubble fraction of rice plants. The leaves of cut fraction for MR 185 straw variety showed higher nutritive quality, in terms of crude protein concentration (6.8%), fiber (ADF 46.8% and NDF 69.5%), total digestible nutrients (50.4%) and digestible energy (2.2 MJ/kg) compared to the stubble and uncut plant parts. Therefore, cut fraction of straw was recommended to be collected for ruminant feed and the stubble could be incorporated into the soil to maintain land productivity for the next crop or other purpose. In another experiment, changes of protein and fiber concentration of rice straw were observed over time. Rice straw was exposed to open weather in the field for 30 days. Nutritive values of rice straw were found to be relatively stable when they were iv exposed to the weather. There was no significant reduction of CP concentration but fiber concentration increased with delaying straw collection from the field. Therefore, farmers could delay straw collection from the field but earlier collection of straw was suggested for feeding ruminants. In the nutritive value improvement study - two straw treatment (urea and steam) methods of rice straw were evaluated. Urea increased CP concentration of treated rice straw by 47% compared to untreated rice straw. In vitro DM and OM digestibility of urea treated rice straw was increased by 29.3% and 35.9%, respectively compared to the untreated rice straw. This was confirmed by the in vitro gas production at a sequential incubation with buffered rumen fluid. Potential gas volume was higher in urea treated rice straw (52.2 ml/200mg) than untreated rice straw (41.9 ml/200mg) and steam treated rice straw (50.9 ml/200mg). Steam treatment caused a significant decrease in lignin (ADL) concentration (30.3%) compared to urea treated rice straw (34.1%) and untreated rice straw (35.0%) due to the effect of high pressure and rapid decompression to weaken the cell wall structure and the release of fermentable sugar from the depolymerized lignin and cell wall matrix. The disruptions and the physical changes in rice straw cell wall structure due to steam treatment enable microbes to penetrate to the cell wall matrix resulting in improved digestibility. In the feed evaluation study – iso-nitrogenous and iso-caloric various formulation of total mixed ration was examined. Three straw treatments (untreated, urea and steam treated) and three levels (40, 55 and 70%) of straw inclusion were used together with other ingredients to make total mixed ration. v In a feeding trial, dry matter intake of the ration and average daily gain of the Malin local-bred lambs was examined. The ration comprising 40% steam treated straw showed highest intake (126.5 g kg-1W0.75) and gave highest daily gain (176.8 g d-1). Untreated straw with 70% inclusion showed lowest intake (71.7 g kg-1W0.75) and gave the lowest weight gain (50.0 g d-1). Steam treated ration increased intake by 27.4% and urea treated ration by 21.5%; average daily gain of the lambs increased by 73.5% in steam and 65.0% in urea treated ration compared to untreated ration. Increasing level of straw inclusion from 40 to 70% reduced intake by 21.1% and weight gain by 38.8%. In the digestibility study, there were no significant differences (P>0.05) in nutritional quality among the rations. No significant differences were also obtained in rate of particulate particle constant, mean retention time and solid flow rate. However, increasing level of straw inclusion tended to increase retention time due to the slower passage rate. Therefore, this study concluded that the rice straw has a potential to be utilized in ruminant feeding system by using straw treatment and improving its nutritive value with the addition of other ingredients. Hence, production of TMR is worth trying and this could conceivably be practiced by large farms for intensive ruminant production.